2015
DOI: 10.1097/shk.0000000000000260
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Serial Lactate Monitoring on Emergency Department Resuscitation Interventions and Clinical Outcomes in Severe Sepsis and Septic Shock

Abstract: Monitoring in the setting of critical illness must be linked to beneficial therapy in order to affect clinical outcome. Elevated serum lactate is associated with an increase in mortality in Emergency Department (ED) patients with severe sepsis and septic shock. The reduction of lactate levels towards normal during acute resuscitation is associated with improved clinical outcomes. The majority of data demonstrating the interventions used to achieve a reduction in lactate levels, and the associated clinical outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 30 publications
0
44
0
Order By: Relevance
“…28 Similarly, other Authors found that using lactate-guided therapy compared with control and found a significant reduction in hospital mortality. 29 supporting the concept that a decrease in elevated lactate concentrations might reflect successful management. In human medicine the speed at which hyperlactatemia resolves with appropriate therapy may be considered a useful prognostic indicator in critically ill, even if lactate alone should not be considered sufficient to judge success or failure of treatment.…”
Section: Lactic Acidosis In Sepsismentioning
confidence: 66%
“…28 Similarly, other Authors found that using lactate-guided therapy compared with control and found a significant reduction in hospital mortality. 29 supporting the concept that a decrease in elevated lactate concentrations might reflect successful management. In human medicine the speed at which hyperlactatemia resolves with appropriate therapy may be considered a useful prognostic indicator in critically ill, even if lactate alone should not be considered sufficient to judge success or failure of treatment.…”
Section: Lactic Acidosis In Sepsismentioning
confidence: 66%
“…In a previous investigation, serial lactate monitoring in patients with severe sepsis and septic shock was associated with improved mortality outside the setting of a randomized trial[19]. The use of serial lactate monitoring seemed to be a surrogate for a “more aggressive” acute resuscitation, as there was a greater use of central venous catheters, as well as monitoring of central venous pressure and mixed venous oxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…This was a retrospective observational cohort study and preplanned secondary analysis of previously published data, reported in accordance with The Strengthening the Reporting of Observational Studies in Epidemiology Statement: Guidelines for Reporting Observational Studies [19,20]. This study was approved by the Human Research Protection Office at the principal investigator’s institution with waiver of informed consent, approval number 201206130.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations